Thermal performance study of a multi-pass solar air heating collector system for drying of Roselle (Hibiscus sabdariffa) - Kareem, M.W. (Elsevier Ltd, 2017)
This article presents a study on the performance of a forced convective multi-pass solar air heating collector (MPSAHC) system assisted with granite as a sensible energy storing matrix. Experimental drying of Roselle was carried out in August 2015 at Solar Energy Research Site of Universiti Teknologi PETRONAS, Malaysia (4.385693° N and 100.979203 S). The present investigation was conducted under the daily average relative humidity, solar irradiance, ambient temperature and wind speed of 64.5, 635.49 Wm−2, 32.24 °C, and 0.81 ms−1, respectively. An average drying rate of 33.57 g (kg m2 h)−1 was achieved while the system optical efficiency, collector efficiency, drying efficiency and moisture pickup efficiency of 70.53, 64.08, 36.22 and 66.95 were obtained, respectively. MPSAHC dryer was 21 h faster with fair color retention when compared to open sun drying approach (OSDA) that was conducted together under the same weather condition. Techno economic analysis reflected a payback period of 2.14 years. However, drying efficiency could be improved if the inlet air humidity can be controlled to favor drying operation. © 2016